Tumor Genotype Determines Phenotype and Disease-related Outcomes in Thyroid Cancer: A Study of 1510 Patients. Issue 3 (September 2015) - Yip, Linwah; Nikiforova, Marina N.; Yoo, Jenny Y.; McCoy, Kelly L.; Stang, Michael T.; Armstrong, Michaele J.; Nicholson, Kristina J.; Ohori, N. Paul; Coyne, Christopher; Hodak, Steven P.; Ferris, Robert L.; LeBeau, Shane O.; et al.
Abstract : Objectives: To correlate thyroid cancer genotype with histology and outcomes. Background: The prognostic significance of molecular signature in thyroid cancer (TC) is undefined but can potentially change surgical management. Methods: We reviewed a consecutive series of 1510 patients who had initial thyroidectomy for TC with routine testing for BRAF, RAS, RET/PTC, and PAX8/PPARG alterations. Histologic metastatic or recurrent TC was tracked for 6 or more months after oncologic thyroidectomy. Results: Papillary thyroid cancer (PTC) was diagnosed in 97% of patients and poorly differentiated/anaplastic TC in 1.1%. Genetic alterations were detected in 1039 (70%); the most common mutations were BRAF V600E (644/1039, 62%), and RAS isoforms (323/1039, 31%). BRAF V600E-positive PTC was often conventional or tall cell variant (58%), with frequent extrathyroidal extension (51%) and lymph node metastasis (46%). Conversely, RAS -positive PTC was commonly follicular variant (87%), with infrequent extrathyroidal extension (4.6%) and lymph node metastasis (5.6%). BRAF V600E and RET / PTC -positive PTCs were histologically similar. Analogously, RAS and PAX8 / PPARG -positive PTCs were histologically similar. Compared with RAS or PAX8/PPARG -positive TCs, BRAF V600E or RET / PTC -positive TCs were more often associated with stage III/IV disease (40% vs 15%, P < 0.001) and recurrence (10% vs 0.7%, P < 0.001; mean follow-up 33 ± 21 mo). Distant metastasis was highest in patients with RET / PTC -positive TC (10.8%, P = 0.02). Conclusions: In this large study of prospective mutation testing in unselected patients with TC, molecular signature was associated with distinctive phenotypes including cancers, with higher risks of both distant metastasis and early recurrence. Preoperative genotype provides valuable prognostic data to appropriately inform surgery. Abstract : Molecular signature associated with thyroid cancer correlate with distinctive tumor phenotypes and disease-free survival rates. The incidence of local and distant metastatic disease was higher in patients with BRAF V600E and RET/PTC positive than with RAS, PAX8/PPARG, and BRAF K601E positive thyroid cancers. Thyroid cancer genotype provides prognostic data that can guide patient care.